2009
DOI: 10.2136/sssaj2008.0079
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the EM38DD and DUALEM‐21S Sensors for Depth‐to‐Clay Mapping

Abstract: Geophysical instruments show great potential for the detailed quantification of soil stratigraphy. In this study, two electromagnetic induction sensors were evaluated on their capacity to map small‐scale variations of the depth to the interface (zin) in a two‐layered soil. On a 2‐ha study site, zin between the silty topsoil and the contrasting clayey subsoil was modeled first by relating the two apparent electrical conductivity (ECa) measurements of the EM38DD sensor to observations of zin obtained by augering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(67 citation statements)
references
References 20 publications
0
66
0
1
Order By: Relevance
“…Each of the aforementioned sensors has distinct operational advantages and disadvantages (Sudduth et al, 2003). Comparative studies have generally revealed close similarities between EC a data collected with different sensors (Doolittle et al, 2001(Doolittle et al, , 2002aSaey et al, 2009a;Sudduth et al, 1999Sudduth et al, , 2003Urdanoz and Aragüés, 2012). However, differences in sensor calibration, depth sensitivity and volume of soil material measured will affect measurements and result in slightly different EC a values.…”
Section: Emi Sensorsmentioning
confidence: 99%
“…Each of the aforementioned sensors has distinct operational advantages and disadvantages (Sudduth et al, 2003). Comparative studies have generally revealed close similarities between EC a data collected with different sensors (Doolittle et al, 2001(Doolittle et al, , 2002aSaey et al, 2009a;Sudduth et al, 1999Sudduth et al, , 2003Urdanoz and Aragüés, 2012). However, differences in sensor calibration, depth sensitivity and volume of soil material measured will affect measurements and result in slightly different EC a values.…”
Section: Emi Sensorsmentioning
confidence: 99%
“…In this study the apparent soil electric conductivity (ECa), was carried out by electromagnetic induction (EMI) sensors, which represents a very useful tool for identifying soil map units and soil properties in respect of clay content (Morari et al, 2009), soil depth (Saey et al, 2009), water content (Davies, 2004;Cousin et al, 2009;Lück et al, 2009;Tromp-van Meerveld and McDonnell, 2009) and water salinity (Doolittle et al, 2001).…”
Section: Pedological Survey and Soil Measurementsmentioning
confidence: 99%
“…Examples of the application of EMI-based ECa measurements include soil salinity (e.g., Doolittle et al, 2001;Heilig et al, 2011), spatial patterns of soil texture (e.g., Abdu et al, 2008;Heil and Schmidhalter, 2012), lateral boundaries between soil types (e.g., Anderson-Cook et al, 2002;James et al, 2003), depth of clay-rich layers (e.g., Saey et al, 2009;Doolittle at al., 1994), clay content (e.g., King et al, 2005;Weller et al, 2007), soil compaction (e.g., Al-Gaadi, 2012;Islam et al, 2014), soil CEC (e.g., Headley et al, 2004;Triantafilis et al, 2009), soil organic carbon (e.g., Martinez et al, 2009;Altdorff et al, 2016), assessment of soil quality (e.g., Johnson et al, 2001;Corwin and Lesch, 2005), detection of buried services (e.g., Won and Huang, 2004;El-Quady et al, 2014), and mapping of active layer thickness in permafrost areas (e.g., Hauck and Kneisel, 2008;Dafflon et al, 2013). ECa measurements are widely used in the context of precision agriculture for, e.g., refining existing soil maps (e.g., Doolittle et al, 2008;Martini et al, 2013), precision farming (e.g., Lück et al, 2009;Scudiero et al, 2015), and harvest zoning (e.g., Frogbrook and Oliver, 2007;Priori et al, 2013).…”
Section: Introductionmentioning
confidence: 99%